Crowding density in urban environment and its effects on emotional responding of pedestrians: using wearable device technology with sensors capturing proximity as well as psychophysiological emotion responses while walking in the street. - Papastefanou, Georgios; Xiang, Luyao; Engelniederhammer, Anna (My University, 2018)
Worldwide urbanization in many areas leads to very high urban density living conditions, for example, in Hong Kong, there are about 40.000 people per km2 (Berlin: 4000 p/km2). Tost (2015) pointed out, mental health is impaired by two main features of high density urban environment: 1. high socio-spatial complexity and heterogeneity. 2. shortening social distance and invasion to personal space. Indeed, the empirical findings on mental load effects mainly are based on aggregate level analyses. However little is known about how high density environment with large crowding in street canyon is affecting individuals in their actual emotional responses and to what extent facilities like parks and open spaces can have a restorative counterbalance to stress experiences. Two theoretical approach are relevant for formulating specific hypothesis. 1. Prospect refuge theory (Appleton, 1984). It seeks to describe why certain environments feel secure and thereby meet basic human psychological needs. 2. Attention restorative theory (Kaplan 1995 , Ulrich 1991). It indicates that greening place would help people to recover from mental fatigue, as it could supply indirect attention resource. From this background, these research will be examined emipirically: 1. How high density urban environment is reflected in specific trajectories of casual crowd encounter and pace of walking and how does it correlate with stress perception and restorative need? 2. Does walking in a park nearby park compensate accumulated stress experience? Does park experience increase stress resilience in coping with high density urban experiences mentioned above? The sample is based on 30 students (age>18) studying and living in Hong Kong since no longer than 3 years. The study uses a within-subject and between-subject measurement design. Subjects were told to walk a selected route is in Tsim Sha Tsui of Hong Kong. The route contains of two parts: urban environment and Kowloon Park. Tsim Sha Tsui is a commerce center in Hong Kong with very high pedestrian density. There are two groups of subjects which will walk the same route but reversed walking sequence. Subject start at meeting point a and go through smartphone with specific tests and questionnaires. After walked one part of the route, they return to meeting point a and repeat it. This pre-post-measurement design is for the aim to guarantee sample homogeneity. At selected spots, there are questions need to be answered. When finished the walking, socio-demographic information will be collected. Continuous measurement of geo-position and casual people encounter is captured automatically by a wearable device combining GPS logging and ambient space cross movement detection by infra-red sensor. Besides adding knowledge to micro processes of high urban density effects on social casual encountering intervening with stress effects and their counterbalancing by park experience, the study will provide findings about reliability and validity of an integrated wearable devices which objectively and ctinuously measures crowd density and its covariation with psychophysiological emotion responses while walking in urban environment.
Keywords: Großstadt; Stadtleben; Bevölkerungsdichte; Bebauungsdichte; Fußgänger; Stressbelastung; Emotion; Sensorische Messung; Messmethode; Neurourbanistik